Effect of Loading Rates on Mechanical Characteristics and Rock Burst Tendency of Coal-Rock Combined Samples - Jiang Hu; Jingang Li (Advances in Materials Science and Engineering)
According to the universal law of thermodynamics, the failure of any substance is closely related to its energy change. Understanding the strain energy and rock burst tendency of rock or coal under different loading rates is critical in many geological projects, such as mining, tunneling, and other underground engineering project. The mechanical and energy evolution characteristics of the coal-rock combined sample under different loading rates of uniaxial compression were numerically investigated. And, the rock burst tendency was also calculated by the Rock Burst Energy Index KE. The results show that with the increase of the loading rate, the total input energy, elastic strain energy, and dissipation energy all show an increasing trend. But the growth trend is different. And, under the five loading rates, the Rock Burst Energy Index KE of the coal-rock combined sample were all between 1.5 ≤ KE < 5. That is, they all have weak rock burst tendency. And the rock burst energy index increases first and then decreases with the increase of loading rates. This study provides references for propulsion speed of working face in the field mining practice.